Application of Gene Editing Technology in Resistance Breeding of Livestock - Sutian Wang; Zixiao Qu; Qiuyan Huang; Jianfeng Zhang; Sen Lin; Yecheng Yang; Fanming Meng; Jianhao Li; Kunli Zhang (Life, 2022)
As a new genetic engineering technology, gene editing can precisely modify the specific gene sequence of the organism’s genome. In the last 10 years, with the rapid development of gene editing technology, zinc-finger nucleases (ZFNs), transcription activator-like endonucleases (TALENs), and CRISPR/Cas9 systems have been applied to modify endogenous genes in organisms accurately. Now, gene editing technology has been used in mice, zebrafish, pigs, cattle, goats, sheep, rabbits, monkeys, and other species. Breeding for disease-resistance in agricultural animals tends to be a difficult task for traditional breeding, but gene editing technology has made this easier. In this work, we overview the development and application of gene editing technology in the resistance breeding of livestock. Also, we further discuss the prospects and outlooks of gene editing technology in disease-resistance breeding.